Anxiolytic and antidepressant like effects of Zamzam water in STZ-induced diabetic rats, targeting oxidative stress, neuroinflammation, BDNF/ERK/CREP pathway with modulation of hypothalamo-pituitary–adrenal axis - Taha, Medhat; Mahmoud, Mohamed Ezzat; Al-Kushi, Abdullah G.; Sarhan, Anas; Abdelbagi, Omer; Baokbah, Tourki A. S.; Babateen, Omar; El-Shenbaby, Ibrahim; Qusty, Naeem F.; Elazab, Sara T. (Frontiers in Neuroscience, 2023)
Introduction Recent studies have reported a strong relationship between diabetes and anxiety- and depression-like behaviors; however, there is a lack of information on the underlying pathophysiology. Alkaline Zamzam water (ZW), which is rich in several trace elements, has neuroprotective properties. This study aimed to investigate the anxiolytic and antidepressant effects of ZW against diabetes-induced behavioral changes and shed light on the possible underlying mechanisms. Methods Forty-eight rats were divided into four experimental groups (n = 12): group I (control group), group II (Zamzam water group), group III (diabetic group), and group IV (diabetic + Zamzam water group). Diabetes was induced by an intraperitoneal injection of 60 mg/kg streptozotocin (STZ). At the end of the experiment, the forced swimming test (FST) was used to assess depression-like effects. The elevated plus maze test (EPMT) and open field test (OFT) were performed to evaluate anxiety-like behavior. Blood levels of the hypothalamic–pituitary–adrenal (HPA) axis were measured, and prefrontal cortex and hippocampal tissue samples were removed for histological, immunohistochemical, ELISA, and Q-PCR analyses. Results ZW significantly decreased the immobility time in the FST, indicating an antidepressant effect (p < 0.001). Additionally, ZW significantly improved the OFT and open field entry (OFE) percentages in the EPMT, increasing center crossing and decreasing grooming and fecal boli in the OFT. This indicated an anxiolytic-like effect in diabetic rats with histological improvement. Interestingly, ZW significantly increased prefrontal cortical and hippocampal levels of antioxidant enzymes and the Nrf2/HO-1 pathway. It also modulated the HPA axis by increasing cortisol and corticotropin-releasing hormone (CRH) levels, with a decrease in ACTH and an increase in monoamine neurotransmitters. Furthermore, diabetic rats that received ZW showed a decrease in the inflammatory markers TNF-α and GFAP by immunohistochemistry and in the mRNA levels of NFκB, IL-1β, and IL6. In addition, ZW downregulated the expression of the BDNF/ERK2/CREP pathway. Conclusion Our results suggested a neuroprotective effect of ZW against diabetes-induced anxiety- and depression-like behaviors and explored the underlying mechanisms. These findings suggest a promising therapeutic strategy for patients with diabetes who experience anxiety and depression.